INVESTMENT COMPONENT OF TRANSNATIONALIZATION DURING COVID-19 PANDEMIC ON THE EXAMPLE OF INTERNATIONAL CORPORATIONS - Shapoval , A.V.; Yakubovskiy , S.O. (The actual problems of regional economy development, 2022)
The article analyzes the general situation of transnationalization over several years highlights the changes at the beginning of the pandemic caused by the spread of Covid-19. It has been established that oscillatory investment dynamics characterize the period from 1990 to 2020 flows at the global level. The impact of global problems on the activities of corporations in 2020 is noted. The main external factors influencing the activities of the investment nature of corporations in this period are the consequences of the coronavirus infection. According to statistics, a significant drop in investment flows in 2020 was presented, but thanks to the activities of transnational corporations in the fight against the global pandemic, an improvement in the situation were predicted in subsequent years. Pharmaceutical corporations have been identified as the leading players in the fight against the pandemic among TNCs due to significant involvement and cooperation with governments, society, and businesses, both at the national and international levels. As a result, pharmaceutical multinationals resumed their presence in the ranking of innovative companies in 2021 in terms of investment in R&D, significantly improving their positions compared to previous years. With the help of a regression model, using the example of a pharmaceutical company, the dependence of a corporation's income on investment in research and development was demonstrated. At the same time, statistical, graphical and comparative analyzes were used in the article. The article analyzes structural changes in R&D investment companies to understand the reorientation of activities. The reorientation in international companies has made it possible to assert the pandemic as a strategic opportunity to develop new products by pharmaceutical companies directly related to the fight against coronavirus infection, the creation of cooperation between companies of different levels, and a change in segmentation in the product line. Furthermore, a timely response to the challenges of the pandemic and a change in tactics allowed pharmaceutical companies to stay afloat and improve their financial performance, and the situation with investment flows in general.